2008
DOI: 10.1016/j.ecoenv.2006.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Corophium orientale as bioindicator for Venice Lagoon: Sensitivity assessment and toxicity-score proposal

Abstract: The 96-h water-only exposure and 10-d sediment toxicity tests with the amphipod Corophium orientale were performed in order to enhance the knowledge about its overall sensitivity and its applicability to Venice Lagoon sediments. The values obtained with cadmium as reference toxicant demonstrated a certain variability of the LC(50); the higher value was found in spring and the lower in late summer. Tests with other pure chemicals (Ni, Total Ammonia, Sodium Dodecyl-Sulphate) showed good discriminatory power; the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 36 publications
(55 reference statements)
2
13
1
Order By: Relevance
“…With regard to TOC content, the results of this study were comparable or even lower than those typically found in organic enriched or eutrophic Mediterranean lagoons with economic rating due to fisheries and aquaculture exploitations, such as Venice lagoon (0.5 to >30% TOC, Picone et al 2008), Fattibello-Spavola (1.2-3.9% TOC, Frascari et al 2002), Orbetello lagoon (2-7% TOC, Lardicci et al 2001;Lenzi et al 2005), Santa Giusta lagoon (0.48-3,9% TOC, Magni et al 2008b), Cabras lagoon (3.4-6.28% TOC, Magni et al 2005;Como et al 2007). Higher value of TOC were also found in Pabellon lagoon on the north west coast of Mexico, surrounded by intensive agricultural area (0.5-11% TOC, Paez-Osuna et al 1998) or Rio Formosa in southern Portugal which has increased nutrient loading due to land runoff and sewage discharges (0.15-8.3% TOC, Mudge et al 1998).…”
Section: Discussioncontrasting
confidence: 38%
“…With regard to TOC content, the results of this study were comparable or even lower than those typically found in organic enriched or eutrophic Mediterranean lagoons with economic rating due to fisheries and aquaculture exploitations, such as Venice lagoon (0.5 to >30% TOC, Picone et al 2008), Fattibello-Spavola (1.2-3.9% TOC, Frascari et al 2002), Orbetello lagoon (2-7% TOC, Lardicci et al 2001;Lenzi et al 2005), Santa Giusta lagoon (0.48-3,9% TOC, Magni et al 2008b), Cabras lagoon (3.4-6.28% TOC, Magni et al 2005;Como et al 2007). Higher value of TOC were also found in Pabellon lagoon on the north west coast of Mexico, surrounded by intensive agricultural area (0.5-11% TOC, Paez-Osuna et al 1998) or Rio Formosa in southern Portugal which has increased nutrient loading due to land runoff and sewage discharges (0.15-8.3% TOC, Mudge et al 1998).…”
Section: Discussioncontrasting
confidence: 38%
“…Similar results were also observed in the whole-sediment test with the amphipod C. insidiosum. It is well known that when using a battery of bioassays for sediment assessment, the use of sediment reworker species is recommended for the high ecological relevance of whole sediment testing (Picone et al 2008). Knowledge about the use of amphipods for sediment toxicity assessment is very wide.…”
Section: Discussionmentioning
confidence: 99%
“…Ten sampling sites within the Lagoon of Venice (Fig. 1) were selected along a gradient of chemical contamination and toxicity, on the basis of previous studies and surveys (MAG.ACQUE-Thetis, 2006;Picone et al, 2008). Three sampling sites (14B -San Pietro in Volta, 19B -Caroman and 24B -Sant'Erasmo) are located near the sea-inlets and characterized by sandy sediments and low levels of contamination.…”
Section: Area Of Studymentioning
confidence: 99%
“…International standard guidelines are available for the selected bioassays (USEPA, 2002;ASTM, 2004;ISO, 2005) and specific protocols were previously developed and validated for the application of the water-phase test in Venice Lagoon (Volpi Ghirardini and Arizzi Novelli, 2001, 2006Losso et al, 2004;Volpi Ghirardini et al, 2005a). The applicability in Venice Lagoon of the amphipod standard protocol for sediment testing was already verified by Picone (2006) and Picone et al (2008). Sediment were investigated for the presence of organic carbon (OC), metals, polynuclear aromatic hydrocarbons (PAH), organo-chlorine pesticides (OCP), hexachlorobenzene (HCB), poly- chlorinated biphenyls (PCB) and aliphatic hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%